(untitled) (Research, Society and Development, 2021)
Brazil, despite being a multicultural country with regard to racial and regional issues, still presents in its clothing the stamped prejudice. Faced with the various episodes of ethnic-racial intolerance that have plagued Brazilian society, we must consider the school as a place for deconstructing stereotypes, building knowledge and learning that aim to break with degenerative behaviors, in search of a social interaction based in respect, tolerance and harmony. Currently, School Physical Education has been working with cultural diversities within its classes, to promote independent and critical students through its content. Thinking about the educational role and referring to Physical Education classes, how could we break the negative and mistaken paradigms that permeate Afro-Brazilian culture? In this sense, the present study aimed to present and analyze the reports of black and black students from a public school about the importance of the Afro-centered curriculum in Physical Education classes. The study is characterized as an applied research, of the action type, which intended to intervene in the social reality of the participants, students of the 1st year of Elementary School I, enrolled in a public school located in Pavuna. Fifty students, aged between 6 and 7 years, participated in the study. The research findings, represented by the records and speeches of students, corroborate the authors who claim that it is important for the curriculum to have aspects related to sociocultural issues of students and the school community in its structures.